Conceptualization of Remote Patient Monitoring Program for Patients with Complex Medical Illness on Hospital Dismissal - Mariam Charkviani, MD; Douglas A. Simonetto, MD; Desiree J. Ahrens, MA; Rachel H. Amundson, MHA; Sarah J. Bell, MSN, MHA; Joel J. Busch, MSN; Natalie A. Caine, MHA; Eric J. Cleveland, MS; Nayantara Coelho-Prabhu, MBBS; Erin F. Barreto, PharmD, MS; Craig E. Daniels, MD; Meredith A. DeZutter, BFA; et al. (Mayo Clinic Proceedings: Digital Health, 2023)
Objective: To describe the creation of a scalable framework for a Remote Patient Monitoring (RPM) program tied to a large medical practice. Patients and Methods: In July 2020, at Mayo Clinic Rochester, we initiated the process to combine human-centered design, health systems engineering, and clinical expertise to develop and refine RPM programs and explore new medical conditions where RPM could be beneficial. We report on the creation of the overarching RPM program, the development of a hybrid nursing model, the technology used for each population, and the lessons learned throughout the process. Results: Four pilot programs for hospitalized patients with cirrhosis, acute kidney injury (AKI), post-pancreatectomy, and post-gastroenterology (GI) procedures were launched. The 4 programs enrolled a range from 0 patients (post-GI procedures) to 91 patients over 5 months (AKI) for RPM programs ranging from 30 days to 96.5 days in average duration. Three of the programs continue enrollment (cirrhosis, AKI, and post-pancreatectomy), and one program was discontinued. Conclusion: RPM can uniquely facilitate the transition from hospital to home, decrease hospital length of stay, and optimize hospital capacity and staffing resources in select scenarios. To achieve positive results at the health care system level, RPM interventions require a change in the model of care. However, not all care models or medical conditions lend themselves to RPM, which should be explored in pilot testing.